Concerns of Indian Mothers with Children Having Severe-to-Profound Hearing Impairment at Diagnosis and after 1–3 Years of Therapy. (5th August 2012) - Rout, Nachiketa; Khanna, Megha
Abstract : Counseling training in graduate programs continues to be underrepresented. If parental queries are not addressed adequately, they keep visiting one doctor after another. Objective . The aim of the study is to identify maternal needs of children with hearing impairment at two stages of habilitation, that is, just after diagnosis (group I) and after receiving 1 to 3 years of language therapy (group II). Methods . Two groups of mothers were asked to speak their queries about aural habilitation of their children. Queries were recorded, summarized, and categorized as per their priorities. Results . Group I mothers wanted to know about how the child would learn to listen and speak (45%), causes of hearing loss (33.7%), understanding the ear and hearing (10.2%), understanding the audiogram (7%), and coping with emotional aspects of hearing loss (5%), while group II parents had priorities concerning speech development (24.5%) followed by child independence and employment (17.3%), schooling (15.6%), problem behaviors (11%), amplification device (9.4%), duration of therapy (8%), future of the child (8%), and questions about how can my child get adjusted to the "normal" world (6%). Conclusions . Culture- and language-specific materials to explain these issues need to be developed.